Educating Uncertainty - Nina Bohm (A+BE: Architecture and the Built Environment)
Transdisciplinary approaches are increasingly prevalent in higher education curricula. These approaches involve partnering with real-world actors to tackle real-world problems, perhaps most notably the contemporary sustainability challenge. How to balance environmental sustainability with social and economic goals is a contested issue, with varying perspectives on the problems and solutions, even among experts. Furthermore, sustainability education is shaped amidst an unpredictable political landscape and yet unknown technological advancements. This diversity of viewpoints, unpredictability, and a lack of knowledge makes uncertainty an inescapable part of transdisciplinary sustainability education.